ANALISIS ROA, DER, DAN NPM TERHADAP HARGA SAHAM PADA PERUSAHAAN JII PERIODE 2015-2019 - Fera Syah Putri; Bayu Wijayantini; Achmad Hasan Hafidzi (Makro : Jurnal Manajemen Dan Kewirausahaan, 2022)
This study aims to determine whether the variables Return On Assets, Debt To Equity Ratio, and Net Profit Margin have an effect on stock prices in companies listed on the Jakarta Islamic Index in 2015-2019. Sources of data used in this study is secondary data in the form of quantitative data. The data analysis used in this research is Multiple Linear Regression. The results of this study indicate that the Return On Assets variable has a significance value greater than 0.05 (0.185 > 0.05), so it can be concluded that Return On Assets has no effect on stock prices. For the Debt To Equity Ratio variable has a significance value less than 0.05 (0.000 < 0.05), it can be concluded that the Debt To Equity Ratio has an effect on stock prices. While the Net Profit Margin variable has a significance value less than 0.05 (0.023 < 0.05), it can be concluded that Net Profit Margin has an effect on stock prices.